Urine angiotensinogen and salt-sensitivity and potassium-sensitivity of blood pressure. Issue 7 (July 2015) - Rebholz, Casey M.; Chen, Jing; Zhao, Qi; Chen, Ji-Chun; Li, Jianxin; Cao, Jie; Gabriel Navar, Luis; Lee Hamm, Lotuce; Gu, Dongfeng; He, Jiang
Abstract : Objective: Urinary excretion of angiotensinogen [urine angiotensinogen (UAGT)] has been proposed as a biomarker of intrarenal renin–angiotensin system activity. We investigated the association between UAGT and salt-sensitivity and potassium-sensitivity of blood pressure (BP) among Genetic Epidemiology Network of Salt Sensitivity study participants. Methods: The intervention consisted of a 7-day low-sodium diet (51.3 mmol sodium/day), 7-day high-sodium diet (307.8 mmol sodium/day), and 7-day high-sodium diet with potassium supplementation (307.8 mmol sodium/day and 60 mmol potassium/day). Twenty-four-hour UAGT was estimated at baseline and at the end of each intervention for 100 randomly selected participants. Results: Median UAGT (μg/24 h) and UAGT-to-creatinine ratio (UAGT/Cr, μg/g) were significantly reduced during the low-sodium and potassium-supplementation interventions and increased during the high-sodium intervention (both P  = 0.01). Baseline log-transformed UAGT and UAGT/Cr ratio were significantly positively associated with BP at baseline and at the end of each intervention. For example, one standard deviation higher log-UAGT/Cr ratio (1.2 μg/g) was associated with a 5.0-mmHg (95% confidence interval 2.3–7.8) higher SBP at the end of the high-sodium intervention, after adjusting for multiple covariates ( P  = 0.003). In addition, one standard deviation higher log-UAGT/Cr ratio was associated with a 1.6-mmHg increase in age-adjusted and sex-adjusted SBP from the low-sodium intervention to the high-sodium intervention (95% confidence interval 0.1–3.1, P  = 0.04). This association was no longer statistically significant after multivariable adjustment. Conclusion: These data indicate that elevated UAGT are associated with BP sodium sensitivity. Augmentation of intrarenal renin–angiotensin system activity may play an important role in developing salt-sensitive hypertension.